Trunk muscle forces and spinal loads in persons with unilateral transfemoral amputation during sit-to-stand and stand-to-sit activities. (March 2019) - Shojaei, Iman; Hendershot, Brad D.; Acasio, Julian C.; Dearth, Christopher L.; Ballard, Matthew; Bazrgari, Babak
Abstract: Background: Alterations and asymmetries in trunk motions during activities of daily living, involving lower extremities, are suggested to cause higher spinal loads in persons with unilateral lower limb amputation. Given the repetitive nature of most activities of daily living, knowledge of the amount of increase in spinal loads is important for designing interventions aimed at prevention of secondary low back pain due to potential fatigue failure of spinal tissues. The objective of this study was to determine differences in trunk muscle forces and spinal loads between persons with and without lower limb amputation when performing sit-to-stand and stand-to-sit tasks. Methods: Kinematics of the pelvis and thorax, obtained from ten males with unilateral transfemoral lower limb amputation and 10 male uninjured controls when performing sit-to-stand and stand-to-sit activities, were used within a non-linear finite element model of the spine to estimate trunk muscle forces and resultant spinal loads. Findings: The peak compression force, medio-lateral (only during stand-to-sit), and antero-posterior shear forces were respectively 348 N, 269 N, and 217 N larger in person with vs. without amputation. Persons with amputation also experienced on average 171 N and 53 N larger mean compression force and medio-lateral shear force, respectively. Interpretation: While spinal loads were larger in persons with amputation, these loads were generally smaller than the reported threshold for spinal tissue injury. However, a rather small increase in spinal loads during common activities of daily living like walking, sit-to-stand, and stand-to-sit may nevertheless impose a significant risk of fatigue failure for spinal tissues due to the repetitive nature of these activities. Highlights: Increased spinal loads across daily activities may cause fatigue failure of spine. Transfemoral amputees experience larger spinal loads during walking than controls. Spinal loads during sit-to-stand and vice versa were estimated for them. Transfemoral amputees experienced larger peak and mean spinal loads than controls.